ANALISIS PENGATURAN HAK IMUNITAS TERHADAP ANGGOTA DEWAN PERWAKILAN RAKYAT (DPR) YANG TERJERAT KASUS HUKUM - Agus Surya Manika; Ni Made Trisna Dewi; A.A. Mas Adi Trinaya Dewi (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2023)
This article discusses the regulation of immunity rights granted to members of the People's Representative Council (DPR) who are involved in legal cases. The main objective of this research is to analyze the regulation and impact of immunity rights on DPR members involved in legal cases. This research utilizes a document analysis method to examine the regulations and laws related to DPR immunity rights, as well as case studies involving DPR members implicated in legal cases. The data used in this research are sourced from legal documents, court rulings, and media reports. The research findings indicate that the immunity rights granted to DPR members provide special legal protection that restricts their detention, arrest, and prosecution during their term in office. However, the use of these immunity rights also raises various controversies, especially when DPR members are involved in legal cases involving corruption or other serious violations.